VD_FINDINFO Jug / 2017 / 336 vom 4. Mai 2017 - VD Tribunal cantonal (2017)
LÉSION CORPORELLE, INJURE, DÉNONCIATION CALOMNIEUSE, SURSIS À L'EXÉCUTION DE LA PEINE | 106 CP, 123 ch. 2 CP, 123 ch. 3 CP, 177 al. 1 CP, 303 CP, 34 CP, 42 CP, 44 CP, 49 CP, 50 CP